From stakeholders to protagonists: an exploratory framework for cultivating prosocial capacities for development - Hedley, Darren Kirk (Frontiers in Sociology, 2024)
The world in 2024 faces numerous interlinked crises, including climate change and water shortages, rising geopolitical tensions, and a new awareness of the risks of pandemics. These crises reverse decades of incremental development progress and humanity’s aspirations embodied in the 2030 Agenda for Sustainable Development, necessitating a more active and collaborative participation of development stakeholders. The magnitude of challenges points to the need for transformational approaches to releasing the potential of stakeholders, which requires building on and extending beyond current best practices in participation and capacity strengthening. What is most needed today is a balanced assessment of the complexity of human nature and a vision that recognizes the prosocial potential of people to harmonize the pursuit of personal interests with a willingness to contribute to social and collective development goals. Prosociality is a capacity that all stakeholders can strengthen—from individuals to institutions to communities (including different forms of social groupings). These stakeholders can become empowered as active protagonists of development, with the potential to work synergistically to achieve the Sustainable Development Goals (SDGs). In order to work with these protagonists, it is important to view them systematically in terms of key characteristics such as their antecedent knowledge, values and culture, stance, agency, roles, relationships, and learning.